Change of cation exchange capacity during the thermal treatment of bentonite and their textural characteristics - Kalbaev, Alisher; Salixanov , Alisher; Seitnazarova Оksana; Abdikamalova Аziza (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article presents a comprehensive study aimed at analyzing the changes in cation exchange capacity (CEC) of bentonite clays during their beneficiation and subsequent thermal treatment. Using X-ray diffraction analysis, key alterations in the mineralogical composition of the bentonite samples were identified, enabling the assessment of the beneficiation efficiency in terms of montmorillonite content and the reduction in proportions of quartz, kaolinite, and illite. Special attention is devoted to the influence of these processes on the cation exchange properties of bentonite, highlighting a significant increase in CEC after beneficiation and the modification of this characteristic depending on the conditions of thermal treatment. Possible mechanisms underlying the observed changes are analyzed, along with their potential application in creating bentonites with specified properties for various fields of use, particularly in the context of adsorption and wastewater treatment.